2022
DOI: 10.1038/s41467-022-31947-4
|View full text |Cite
|
Sign up to set email alerts
|

Lactational delivery of Triclosan promotes non-alcoholic fatty liver disease in newborn mice

Abstract: Here we show that Triclosan (TCS), a high-volume antimicrobial additive that has been detected in human breastmilk, can be efficiently transferred by lactation to newborn mice, causing significant fatty liver (FL) during the suckling period. These findings are relevant since pediatric non-alcoholic fatty liver disease (NAFLD) is escalating in the United States, with a limited mechanistic understanding. Lactational delivery stimulated hepatosteatosis, triglyceride accumulation, endoplasmic reticulum (ER) stress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…TCS could interfere with reproductive health through oxidative stress [58], hormonal dysregulation [59], germ cell autophagy and apoptosis, steroidogenesis suppression [60], and mitochondrial dysfunction [61]. Long-term exposure to TCS might have unfavorable health effects on the liver, and it could perturb liver metabolic function, aggravate liver fibrosis, accelerate hepatocellular carcinoma development through lipid metabolism disorder [62], induce oxidative stress, facilitate mitochondrial dysfunction [63], and modulate hepatocyte apoptosis [64].…”
Section: Triclosan Toxicologymentioning
confidence: 99%
“…TCS could interfere with reproductive health through oxidative stress [58], hormonal dysregulation [59], germ cell autophagy and apoptosis, steroidogenesis suppression [60], and mitochondrial dysfunction [61]. Long-term exposure to TCS might have unfavorable health effects on the liver, and it could perturb liver metabolic function, aggravate liver fibrosis, accelerate hepatocellular carcinoma development through lipid metabolism disorder [62], induce oxidative stress, facilitate mitochondrial dysfunction [63], and modulate hepatocyte apoptosis [64].…”
Section: Triclosan Toxicologymentioning
confidence: 99%
“…Univariate analysis identified a total of 44 proteins that were changed with unadjusted P <0.05 (Figure 3B and Supplementary Table 7). Notably, the protein with the largest fold decrease in the eIF2B HOM CSF was MUP17 (log 2 fold change (FC): -1.3, adjusted P <0.05), a major urinary protein (MUP) and a member of the broader lipocalin protein family, which has been shown to be decreased by ER stress (Weber, Yang et al 2022). Several proteins associated with microglial activation (PLA2G7, CSF1R, LYSZ, and SIRPA) and intracellular organelle associated proteins (CPE, CTSB, CLSTN1, CTSD, HEXA, GM2A, and ALDH2) were also higher in homozygous mice relative to wild-type controls (Figure 3B and Supplementary Table 7).…”
Section: Proteomic Analysis Reveals Distinct Brain and Csf Signatures...mentioning
confidence: 99%
“…Epidemiological studies have detected TCS in human tissue samples, including breastmilk ( 4 , 5 , 6 ). Chronic TCS exposure to adult mice has been associated with the development of hepatocellular carcinoma (HCC) ( 7 ), nonalcoholic fatty liver disease (NAFLD) ( 8 , 9 ), and ulcerative colitis ( 5 ). However, the impact of TCS exposure on the pathophysiology of cellular function is just starting to be understood.…”
mentioning
confidence: 99%
“…Previous studies have shown that TCS administration activates the integrated stress response (ISR) in the liver ( 8 , 9 ). The ISR is a signaling network that helps the cell adapt to a host of variable environments which are focused on maintaining cell homeostasis ( 25 , 26 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation